Effects of Coronavirus Disease-2019 Pandemic and "New Normal" on the Orthopedic Outpatient Clinic Practice - Çağdaş Biçen; Mehmet Aykut Türken (Galenos Yayinevi, 2021)
Objective:This study aimed to evaluate the effects of the coronavirus disease-2019 pandemic on the orthopedic outpatient clinic, including an investigation of the number, changes in complaints, and demographics of patients.Materials and Methods:Data of patients who visited the orthopedic outpatient clinic at our hospital within four periods were evaluated. Period 1 was between March and May 2019, period 2 was between June and August 2019, period 3 was between March and May 2020, and period 4 was between June and August 2020. Data of patients were recorded for each period including age, gender, number, and International Classification of Diseases 10th Revision codes for comparative analysis.Results:This study included 7,120 patients who were admitted to the orthopedic outpatient clinic within the four periods. The lowest number of patients (1,119) who visited the outpatient clinic was observed in the three months following the pandemic declaration (period 3), in March 2020, whereas the highest number (2,149) was observed in the three months following the lifting of restrictions, in June 2020 (period 4). No significant difference was observed in the age between the four periods (p=0.945). However, a difference was found between the periods for patients aged ≥65 years. Reasons for admission were also different between the periods. In period 3, admissions due to traumatic reasons were statistically higher compared with the other three periods (p<0.001, p=0.003, p<0.001).Conclusion:It was observed that the number of patients visiting the orthopedic outpatient clinic increased after the restrictions were lifted. Outpatient clinic management must be organized in a way that prevents contamination and preserves efficient outpatient support.